Evaluation on the Challenges of Modern Car Maintenance in Nigeria - Omosule, Nenuwa Isaac; Olusegun, Adepo Samuel; Abiodun, Raimi Oluwole; Feyisetan, Fapetu Oluseyi (Asian Review of Mechanical Engineering, 2017)
The paper evaluated on the challenges of modern car maintenance in Owo metropolis, Nigeria. The study employed primary source of information through the aid of a well-structured questionnaire that was distributed to respondents who are modern car users of various models and types. Convenient sampling technique was adopted to select the total number of respondents for the study. Fifty (50) sample of the questionnaire were produced while only forty six (46) were retrieved back after proper administering by the modern car users. The collected data were analyzed using both descriptive and inferential statistic as the statistical tools with the aid of Statistical Package for Social Science (SPSS), version 17.0. The findings revealed that the type of maintenance approach adopted for the brake fluid, engine oil, coolant, power steering/transmission fluid, battery fluid & terminal, vehicle lighting and air filter/tyre shows a significant distribution in correcting maintenance challenges of modern cars which in turns is significantly reflected on the car maintenance cost through adequate and proper allocation cost to the servicing of the cars by the users. The study concludes that modern car users ensure possible measures in correcting challenges in their cars through adequate servicing and reasonable maintenance cost.